Butterfly boy : memories of a Chicano mariposa - González, Rigoberto (Writing in Latinidad., 2006)
"Heartbreaking, poetic, and intensely personal, this is a unique coming-out and coming-of-age story of a first-generation Chicano who trades one life for another, only to discover that history and memory are not exchangeable or forgettable. Growing up among poor migrant Mexican farmworkers, González also faces the pressure of coming-of-age as a gay man in a culture that prizes machismo. Losing his mother when he is twelve, González must then confront his father's abandonment and an abiding sense of cultural estrangement. His only sense of connection gets forged in a violent relationship with an older man. By finding his calling as a writer, and by revisiting the relationship with his father during a trip to Mexico, González finally claims his identity at the intersection of race, class, and sexuality. The result is a leap of faith that every reader who ever felt like an outsider will immediately recognize"--From publisher description.